Response Surface Optimization for Antioxidant Extraction from Jackfruit (Artocarpus heterophyllus Lam.) Seed and Pulp (Journal of Scientific Research, 2020)
The maximum yield of antioxidant activity of freeze-dried jackfruit seeds and pulps was optimized in experimental conditions using response surface methodology. Temperature (°C), time (min) and solvent types (mL) were selected as three independent variables. DPPH (2,2-diphenyl-1-picrylhydrazyl radical), TPC (total phenolic content) and FRAP (ferric reducing antioxidant power) were considered for the antioxidant activity. DPPH, TPC and FRAP values of seed ranged from 45-67.90 %, 2.27-5.42 mg GAE/100 g DM and 63.30-156.39 mg AAE/100 g DM, respectively while those of pulp were 49-72.14 %, 2.109-5.02 mg GAE/100 g DM and 54.90-298.00 mg AAE/100 g DM respectively. The response surface optimization revealed that the optimum conditions for maximum antioxidant activity in seeds were at 65 °C, 10 min and acetone as solvent with 8.76 % DPPH, 2.81 mg GAE/100 g DMTPC, 149.99 mg AAE/100 g DM FRAP and 0.99 desirability whereas that of pulp were at 50°C, 10 min and acetone as solvent with 45.42 % DPPH, 3.06 mg GAE/100 g DMTPC, 129.05 mg AAE/100 g DM FRAP and 0.99 desirability. Extraction of antioxidants from jackfruit seed and pulp can be performed more efficiently up to the maximum yield by maintaining the optimum conditions pinpointed in this study.